Antioxidant, Cytotoxic, and Antiproliferative Activities and Total Polyphenol Contents of the Extracts of Geissospermum reticulatum Bark. (29th June 2016) - Sajkowska-Kozielewicz, Joanna J.; Kozielewicz, Paweł; Barnes, Nicholas M.; Wawer, Iwona; Paradowska, Katarzyna
Abstract : Geissospermum species are medically important plants due to their health-promoting effects. The objective of this study was to determine the antioxidant ability and antiproliferative and cytotoxic effects of infusions, tinctures, and ethanolic extracts of Geissospermum reticulatum barks in relation to the contents of total phenolics and flavonoids. Seven samples of barks were collected in various regions of Peruvian Amazonia. We found that the amount of total phenolics in the studied products varied from 212.40± 0.69 to 1253.92± 11.20 mg GAE/kg. In our study there is a correlation (R 2 = 0.7947 ) between the results of antioxidants assays: FRAP and ORAC for tinctures, infusions, and ethanolic extracts of G. reticulatum barks. We have also observed antiproliferative activities of the ethanolic extracts on normal T-cells. These extracts have caused death on malignant cell lines (THP-1 and HL-60) and this data correlates well with their antioxidant capacity measured by ORAC method. Interestingly, the highest concentration of the ethanolic extract was not toxic in the zebrafish embryo developmental assay. Our results indicate that G. reticulatum is rich in antioxidants and have cytotoxic and antiproliferative properties. The data suggests potential immunosuppressive role of the extracts. This is the first study presenting the results of chemical and biological analysis of multiple preparations from G. reticulatum .